Health Care Worker Perspectives of HIV Pre-exposure Prophylaxis Service Delivery in Central Uganda - Muwonge, Timothy R.; Nsubuga, Rogers; Ware, Norma C.; Wyatt, Monique A.; Pisarski, Emily; Kamusiime, Brenda; Kasiita, Vicent; Nalukwago, Grace Kakoola; Brown, Charles; Nakyanzi, Agnes; Bagaya, Monica; Bambia, Felix; et al. (Frontiers in Public Health, 2022)
Background Scale-up of HIV pre-exposure prophylaxis (PrEP) services in Uganda is ongoing. However, health care workers (HCWs) may not be aware of PrEP nor what offering this service entails. We explored the impact of standardized HCW training on the knowledge and perspectives of PrEP service delivery in Uganda. Methods We recruited HCWs from facilities that offered HIV-related services in Central Uganda. Using the Uganda Ministry of Health curriculum, we trained HCWs on PrEP services. We collected data about PrEP knowledge, preparedness, and willingness to deliver PrEP to multiple key populations before the training, immediately after the training, and >6 months later (exit). We additionally conducted 15 qualitative interviews after the exit survey. Quantitative data were analyzed by Fisher exact test, while qualitative interview data were analyzed inductively. Results We recruited 80 HCWs from 35 facilities in urban (N = 24, 30%), peri-urban (N = 30, 37%), and rural (N = 26, 33%) areas. Most HCWs were nurse counselors (N = 52, 65%) or medical/clinical officers (N = 15, 18%). Surveys indicated that awareness of PrEP increased after the training and remained high. Knowledge of PrEP (i.e., as an effective, short-term antiretroviral medication to use before HIV exposure for people at high risk) generally increased with training, but significant gaps remained, and knowledge decreased with time. Most HCWs recommended PrEP for female sex workers and HIV serodifferent couples, as well as other key populations. We observed increases in the number of HCW who felt their facility was prepared to cater for HIV prevention and provide PrEP, but this view was not universal. HCWs believed in PrEP effectiveness and embraced it as an additional HIV prevention method. Concerns included patient adherence and behavioral risk compensation. HCWs noted challenges in PrEP delivery in terms of inadequate clinic preparedness, infrastructure, staff capacity, and poor attitudes toward key populations by untrained health workers. They felt further training was needed to ensure a smooth scale-up of services without stigmatization. Conclusions Standardized training improved knowledge, willingness, and preparedness to offer PrEP services among most HCWs in Central Uganda. Ongoing training will be needed to optimize PrEP delivery services and expand delivery to levels needed for population-level impact.